Territorialização da indústria automobilística em Catalão e as mudanças no trabalho - (:unkn) unknown (Universidade Federal de Goiás, 2011)
The spatial changes promoted by the productive restructuring of capital, profoundly change the relationship between capital and labor in contemporary, advertising a new phase of expansion and capital accumulation. Reflecting this new dynamic, the geographic mobility of capital has led to industrial decentralization to regions until then little industrialized. This is the case of territorialization of the automotive industry in Catalão that, from the company MMC Automotores do Brazil S/A , representative group of Mitsubishi Motors in the country, located in Catalão (GO) in 1997/1998, sets a new standard reproduction of capital in Southeast Goiás. Nowadays the MMC with their outsourced employ approximately 3,000 (three thousand) workers, which, in the vast majority, are represented by "Sindicato dos Trabalhadores Metalúrgicos de Catalão" (SIMECAT), which was founded in June 2004. The precariousness of work, the new methods of organizing production, the various social control mechanisms, among which stand out Profit Sharing and Results, the teamwork permeated by the discourse of cooperation, outsourcing and hiring of workers of several cities in the Catalão Microregion, show that the geographical expansion of capital deeply reaches into the working class, especially the capacity for organization and mobilization. However, the resistance from SIMECAT also identifies that, even multifaceted and fragmented, the workers point to the need for social emancipation. So, the objective of this research is to understand the spatial changes caused by territorialization of the automobile industry in Catalão and the changes for the job, understanding that this phenomenon is limited to the logic of the process of productive restructuring of capital. For this, the methodology used in this research consists of three stages: theoretical research, documentary research and field research, interconnected, by the theoretical that structure all the work. In addition to the literature review was also held consultation on various documents and data from agencies like the Labor Ministry, the IBGE, the SEPLAN/GO, SEFAZ/GO and others, and was made the collect of informations through interviews and questionnaires, particularly with the MMC company workers, leaders of SIMECAT and public authorities who represent Catalão City Hall and DIMIC.
The territorialisation in the automotive industry Catalão and the changes in work
Keywords: Reestruturação produtiva do capital; Indústria automobilística; Transformações espaciais; Mudanças no trabalho; Economic restructuring of capital; Automotive industry; Spatial transformations; Changes in work; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA